Economics - Mankiw, N. Gregory, 1958-; Taylor, Mark P., 1958- (Hampshire : Cengage Learning EMEA, 2010)
This Special edition of Mankiw and Taylor's "Economics" provides highly topical and in-depth coverage of the global financial crisis of 2007-2009. Two new chapters are included: one on the causes of the recession and one on the remedies available to resolve it. Using a rich array of real-life examples, these new chapters provide students with up to date, real world insights into economic crises. Alongside these two new chapters, several of the existing chapters have been carefully revised and updated to clarify and enhance their content, and further expand students' knowledge of economic theory. All of the features that made the original edition so successful and well-regarded have been retained including the classic Ten Principles approach to economics introduced in Chapter One and then referred to throughout the book, the distinctly European flavour including reference to UK and European institutions and policy, familiar terminology and cultural references, predominant use of the euro in discussions and UK and European case studies and press extracts.
Special edition with coverage of the world financial crisis
Keywords: Economics